“They don't care about people; they only care about the money”: the effects of border enforcement, commodification and migration industries on the mobility of migrants in transit through Mexico - Willers, Susanne (Frontiers in Sociology, 2023)
The article analyses the entanglement of border enforcement and anti-smuggling policies and its effects on the mobility of refugees and migrants in Mexico along the lines of inequality such as race, class, gender and nationality and its intersections. How does border enforcement affect the mobility of migrants and refugees? And how does it impact on their reliance on other actors, for example, migration industries or transnational networks? As has been shown, externalisation of borders affects undocumented migrants and refugees, as it exposes them to multiple violences during transit, yet there has been less research on the impact of the border and migration regime on the social construction of inequality and their relation to the mobility capacity as a mayor tool of agency. Based on former fieldwork (throughout 2013, 2014, 2018 and 2019) and an analysis of the pandemic context, the article seeks to explore the relationship between migration enforcement and the mobility strategies of forced migrants, particularly on women. The objective of the following article is two-fold: First, it aims to analyse how border enforcement produces internal bordering and the vulnerability of forced migrants; Second, it aims to analyse the bodily experiences of women in transit and how internal bordering shapes power hierarchies of the actors in the field of mobility in Mexico. By doing so, it aims to contribute to our understanding of how the governmentality of mobility and the resulting violence in the field of mobility are interconnected. It shows how women negotiate mobility in social interactions with different actors and how they confront limitations arising from the social production of racialized otherness in places of transit or temporal settlement.